LATS suppresses mTORC1 activity to directly coordinate Hippo and mTORC1 pathways in growth control - Gan, Wenjian (Nat Cell Biol, 2020)
The Hippo and mTORC1 pathways are the two predominant growth-control pathways that dictate proper organ development. We therefore explored a possible crosstalk between these two functional relevant pathways to coordinate their growth-control functions. We found that the LATS1/2 kinases, the core component of the Hippo pathway, phosphorylate Ser606 of Raptor, an essential component of mTORC1, to attenuate mTORC1 activation through impairing Raptor interaction with Rheb. The phosphomimetic Raptor-S606D knock-in mutant leads to a reduction in cell size and cell proliferation. Compared to Raptor(+/+) mice, Raptor(D/D) knock-in mice exhibit smaller liver and heart, and a significant inhibition of Nf2 or Lats1/2 loss-induced elevation of mTORC1 signaling and liver size. Thus, our study reveals a direct link between the Hippo and mTORC1 pathways to fine-tune organ growth.